2010
DOI: 10.2319/072109-402.1
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels in Gingival Crevicular Fluid During Orthodontic Tooth Movement

Abstract: Objectives: To test if leptin can be detected in the gingival crevicular fluid (GCF) around moving teeth, and to determine whether any changes occur during orthodontic tooth movement. Materials and Methods: An upper canine requiring distal movement served as the test tooth; the contralateral canine was used as a control tooth. The control tooth was included in the orthodontic appliance, but was not subjected to the orthodontic force. GCF sampling from the distal sites of the test and control teeth was done at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 28 publications
(48 reference statements)
0
69
4
1
Order By: Relevance
“…[13][14][15] After force application (T 1 ), the mean leptin concentration showed an initial increase but then declined at T 2 to a level even lower than the baseline value (T 0 ) both in normal weight and overweight individuals. However, this rise and fall in the leptin concentration during one cycle of orthodontic force application was contrary to results obtained by Dilsiz et al, 28 who showed a decrease in leptin concentration 1 hour after force application. Studies have demonstrated that, after force application, several proinflammatory cytokines tend to increase in the first 24 hours.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…[13][14][15] After force application (T 1 ), the mean leptin concentration showed an initial increase but then declined at T 2 to a level even lower than the baseline value (T 0 ) both in normal weight and overweight individuals. However, this rise and fall in the leptin concentration during one cycle of orthodontic force application was contrary to results obtained by Dilsiz et al, 28 who showed a decrease in leptin concentration 1 hour after force application. Studies have demonstrated that, after force application, several proinflammatory cytokines tend to increase in the first 24 hours.…”
Section: Discussioncontrasting
confidence: 56%
“…27 Recent studies evaluated leptin levels in gingival crevicular fluid during orthodontic tooth movement and found that the leptin level is decreased during orthodontic tooth movement. 28 Leptin is also expressed in saliva, and there is a strong positive correlation between leptin concentration from saliva and serum samples. 11 Analysis of leptin in saliva is noninvasive, and its concentration is high compared with plasma samples.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier findings concluded that leptin at high local concentrations protects the host from inflammation and infection as well as maintaining bone levels. It has been also suggested that leptin plays a significant role in bone formation by its direct effect on osteoblasts (Alparslan et al 2010). This pilot study aimed to study leptin in saliva and its association with tooth movement during initial orthodontic alignment.…”
mentioning
confidence: 99%
“…Detection of the leptin level in GCF at sites under orthodontic movement had been tested and it was found that the concentration of leptin in GCF is decreased by orthodontic tooth movement 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation